MODERN LOOKS TO HISTOLOGICAL FEATURES OF ORGANS OF MALE REPRODUCTIVE SYSTEM - Вільхова, О.В. (World of Medicine and Biology, 2016)
An organism of man is the difficult system of organs, among that an important place is occupied by the reproductive system responsible for continuation of human family. Primary sexual characters appear in an embryonic period, and secondary - in a period of pubescence. Under the action of hormones, during pubescence, there are intensive development and forming of organs of the male reproductive system in an organism. Study of the features this system in a norm gives an opportunity of the best understanding of treatises and violation functioning of one or another organ of the male reproductive system.
Keywords: male reproductive system; testis; seminiferous tubules; Sertoli cells; cells of Leydig; seminal vesicles; prostate gland